4‐Sulfamoylphenylalkylamides as Inhibitors of Carbonic Anhydrases Expressed in Vibrio cholerae. (18th October 2021) - Mancuso, Francesca; De Luca, Laura; Bucolo, Federica; Vrabel, Milan; Angeli, Andrea; Capasso, Clemente; Supuran, Claudiu T.; Gitto, Rosaria
Abstract: A current issue of antimicrobial therapy is the resistance to treatment with worldwide consequences. Thus, the identification of innovative targets is an intriguing challenge in the drug and development process aimed at newer antimicrobial agents. The state‐of‐art of anticholera therapy might comprise the reduction of the expression of cholera toxin, which could be reached through the inhibition of carbonic anhydrases expressed in Vibrio cholerae (VchCAα, VchCAβ, and VchCAγ). Therefore, we focused our interest on the exploitation of sulfonamides as VchCA inhibitors. We planned to design and synthesize new benzenesulfonamides based on our knowledge of the VchCA catalytic site. The synthesized compounds were tested thus collecting useful SAR information. From our investigation, we identified new potent VchCA inhibitors, some of them displayed high affinity toward VchCAγ class, for which few inhibitors are currently reported in literature. The best interesting VchCAγ inhibitor ( S )‐N‐(1‐oxo‐1‐((4‐sulfamoylbenzyl)amino)propan‐2‐yl)furan‐2‐carboxamide (40 ) resulted more active and selective inhibitor when compared with acetazolamide (AAZ) as well as previously reported VchCA inhibitors. Abstract : Design in the time of cholera : Carbonic anhydrases (CAs) catalyze the reversible hydration of CO2 in Vibrio cholerae, so VchCAs are attractive targets for the treatment of cholera. A structure‐inspired drug design of benzenesulfonamides led to identification of potent and selective VChCAα and VChCAγ inhibitors as potential antimicrobial agents. Further studies might furnish insight into the future design of effective agents able to fight antimicrobial resistance issue.